Radiation transmission, leakage and beam penumbra measurements of a micro‐multileaf collimator using GafChromic EBT film - García‐Garduño, Olivia Amanda (J Appl Clin Med Phys, 2008)
Micro‐multileaf collimator systems coupled to linear accelerators for radioneurosurgery treatments require a rigorous dosimetric characterization in order to be used in 3D conformal and intensity modulated stereotactic radiosurgery and radiotherapy applications. This characterization involves high precision measurements of leaf transmission, leakage and beam penumbra through the collimation system and requires the use of detectors with high spatial resolution, high sensitivity and practically no energy dependence. In this work the use of GafChromic EBT radiochromic film to measure the basic dosimetric properties of the m3‐mMLC (BrainLAB, Germany) micro‐multileaf collimator system integrated to a 6 MV linear accelerator, is reported. Results show that average values of transmission and leakage radiation are [Formula: see text] and [Formula: see text] , respectively. The 80–20% beam penumbra were found to be [Formula: see text] along the leaf side (perpendicular to leaf motion) and [Formula: see text] along the leaf end (parallel to leaf motion) using square field sizes ranging from 9.1 to 1.8 cm. These measurements are in agreement with values reported in the literature for the same type of mMLC using different radiation detectors. PACS number: 87.56.N‐